Effects of sodium thiosulfate versus observation on development of cisplatin-induced hearing loss in children with cancer (ACCL0431): a multicentre, randomised, controlled, open-label, phase 3 trial. Issue 1 (January 2017) - Freyer, David R; Chen, Lu; Krailo, Mark D; Knight, Kristin; Villaluna, Doojduen; Bliss, Bonnie; Pollock, Brad H; Ramdas, Jagadeesh; Lange, Beverly; Van Hoff, David; VanSoelen, Michele L; Wiernikowski, John; et al.
Summary: Background: Sodium thiosulfate is an antioxidant shown in preclinical studies in animals to prevent cisplatin-induced hearing loss with timed administration after cisplatin without compromising the antitumour efficacy of cisplatin. The primary aim of this study was to assess sodium thiosulfate for prevention of cisplatin-induced hearing loss in children and adolescents. Methods: ACCL0431 was a multicentre, randomised, open-label, phase 3 trial that enrolled participants at 38 participating Children's Oncology Group hospitals in the USA and Canada. Eligible participants aged 1–18 years with newly diagnosed cancer and normal audiometry were randomly assigned (1:1) to receive sodium thiosulfate or observation (control group) in addition to their planned cisplatin-containing chemotherapy regimen, using permuted blocks of four. Randomisation was initially stratified by age and duration of cisplatin infusion. Stratification by previous cranial irradiation was added later as a protocol amendment. The allocation sequence was computer-generated centrally and concealed to all personnel. Participants received sodium thiosulfate 16 g/m 2 intravenously 6 h after each cisplatin dose or observation. The primary endpoint was incidence of hearing loss 4 weeks after final cisplatin dose. Hearing was measured using standard audiometry and reviewed centrally by audiologists masked to allocation using American Speech-Language-Hearing Association criteria but treatment was not masked for participants or clinicians. Analysis of the primary endpoint was by modified intention to treat, which included all randomly assigned patients irrespective of treatment received but restricted to those assessable for hearing loss. Enrolment is complete and this report represents the final analysis. This trial is registered withClinicalTrials.gov, numberNCT00716976 . Findings: Between June 23, 2008, and Sept 28, 2012, 125 eligible participants were randomly assigned to either sodium thiosulfate (n=61) or observation (n=64). Of these, 104 participants were assessable for the primary endpoint (sodium thiosulfate, n=49; control, n=55). Hearing loss was identified in 14 (28·6%; 95% CI 16·6–43·3) participants in the sodium thiosulfate group compared with 31 (56·4%; 42·3–69·7) in the control group (p=0·00022). Adjusted for stratification variables, the likelihood of hearing loss was significantly lower in the sodium thiosulfate group compared with the control group (odds ratio 0·31, 95% CI 0·13–0·73; p=0·0036). The most common grade 3–4 haematological adverse events reported, irrespective of attribution, were neutropenia (117 [66%] of 178 participant cycles in the sodium thiosulfate group vs 145 [65%] of 224 in the control group), whereas the most common non-haematological adverse event was hypokalaemia (25 [17%] of 149 vs 22 [12%] of 187). Of 194 serious adverse events reported in 26 participants who had received sodium thiosulfate, none were deemed probably or definitely related to sodium thiosulfate; the most common serious adverse event was decreased neutrophil count: 26 episodes in 14 participants. Interpretation: Sodium thiosulfate protects against cisplatin-induced hearing loss in children and is not associated with serious adverse events attributed to its use. Further research is needed to define the appropriate role for sodium thiosulfate among emerging otoprotection strategies. Funding: US National Cancer Institute.